Assessment of level, extent and factors influencing Striga infestation of cereals and cowpea in a Sudan Savanna ecology of northern Nigeria - Kamara A. Y.; Friday, E.; Jibrin M.; Jibrin, G. T.; Ibrahim, T. (Elsevier, 2014)
Infestation of cereals and cowpeas by Striga species constitute a major constraint to increased crop productivity in the savannas of northern Nigeria. Field surveys were undertaken in Jigawa State, Nigeria in 2012 to assess (i) the level and extent of Strgia infestation of cereal and cowpea fields (ii) the severity of Striga attack on crops and (iii) to determine the factors associated with Striga infestation of crop fields. The study was conducted in 48 communities. Eight farmer's fields were sampled in each community along two intersecting transects. Striga hermonthica incidence ranged from 58 to 100% in sorghum fields and from 0 to 100% in millet fields. In sorghum and millet fields, number of emerged Striga plants ranged from 4750 to 431,500 and 0 to 251,750 plants ha?1 respectively. For cowpea, S. gesnerioides population ranged from 1625 to 105,375 plants ha?1. The severity of Striga attack on sorghum was devastating in all the communities studied. Except in a few cases, all cowpea plants in fields surveyed in most communities were attacked by S. gesnerioides. Field infestation was largely related to poor soil fertility. Stepwise multiple regression identified latitude, pH, available P, Cu and exchangeable K as potentially most important in explaining observed variations in S. hermonthica infestation in sorghum fields. For millet fields, soil pH, available P, Zn and latitude accounted for most of the variations in Striga population whereas latitude, total N, organic C, exchangeable Ca, ECEC, pH, available Mn and Cu accounted for most of the observed variations in S. gesnerioides population in cowpea fields. Our study showed that Striga is a major problem in Jigawa State with almost all the cowpea, sorghum and millet fields infested with the parasite. Improved soil fertility management technologies and Striga-resistant crop varieties are needed to address the menace of Striga in the State.